Rejuvenating organic soil behavior with crushed waste concrete: experimental and mineralogical investigations - Almsedeen, Ayah; Mohd Fakhrurrazi, Ishak; Nurmunira, Muhammad; Siddiqua, Sumi; Muhammad Nizam, Zakaria (Penerbit UTHM, 2024)
Urban regions are currently grappling with the mounting challenge of managing substantial volumes of solid waste, especially from building and demolition materials. This study explores the utilization of Crushed Waste Concrete (CWC), a substantial component of solid waste, for organic soil stabilization. Various percentages (10%, 15%, and 20%) of crushed waste concrete were added to organic soil. Subsequently, a comprehensive series of laboratory tests were conducted, including compaction tests using the standard Proctor test, Unconfined Compressive Strength (UCS) tests, and Physicochemical assessments comprising of pH, Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray (EDX), and X-ray diffraction (XRD) analyses. The results of the experimental tests revealed interesting outcomes. As the percentage of crushed concrete increased, there were corresponding increases and decreases in the organic soil's maximum dry density and optimum water content, respectively. Notably, the UCS values of the organic soil exhibited an enhancement of approximately 594% when the CWC percentage was 10%. The SEM-EDX and XRD analyses provided valuable insights, indicating an improvement in the soil structure and the presence of new cementitious materials such as calcium-aluminate-hydrate (CAH) and calcium-silicate-hydrate (CSH) resulting from the interaction between crushed waste concrete and organic soil. This study demonstrates the potential of crushed waste concrete as an effective agent for organic soil stabilization, offering a sustainable approach for repurposing solid waste and mitigating soil-related challenges in urban regions. The findings suggest promising prospects for further exploration and application of this eco-friendly technique in civil engineering and construction practices, contributing to waste reduction and environmental preservation.